Model Pengembangan Kreativitas dan Inovasi dalam Membentuk Entrepreneur di Era Ekonomi Digital - Hamdan Hamdan (University of Merdeka Malang, 2019)
This study aims to develop a model of creativity and innovation in building the entrepreneurial spirit. The population are 145 young people from the study group in Anyer District, Serang Regency. The location selection is based on the fact that young people in that area are more interested in working on the Cilegon industrial area than become entrepreneurs, while business opportunities in the digital economy era are wide open to the younger generation. The research data is collected by giving tests, questionnaires, guidelines, observations, interviews and documentation studies. The data is analyzed using descriptive analysis, percentage, with non-parameter statistics with Microsoft Excel, and SPSS 19. The results of this study show that: 1) model planning is ready to be carried out based on theory and empirical research results in field of entrepreneurship courses in structured concept;. 2) the process of applying this model is carried out in community learning groups through three stages: introductory material, model development, and model testing; 3) the model that encourages the development of creativity and entrepreneurial innovation towards community learning groups is a training model oriented to build the entrepreneurial spirit in the digital economic era; 4) This training model enables the creation of entrepreneurial institutions in the digital economic era that require more creativity and innovation.https://doi.org/10.26905/jmdk.v7i1.2548